A Novel Dual-Broadband Circularly Polarized Patch Antenna for Precise Satellite Navigation. (20th December 2019) - Lin, Fumin; Zhang, Liangxian; Cai, Huiping; Liu, Mingjian; Li, Xiaopeng; Xiao, Yujie
Abstract : This paper presents a novel dual-band circularly polarized patch antenna for precise satellite navigation. The radiation elements are composed of the inner cross-shaped patch and the outer annular patch which are printed on the same surface of one substrate. Two patches work in different bands, respectively, and emit dual-band circularly polarized radiation. In order to obtain a more compact antenna to meet the application of precise satellite navigation, we vertically place four metal cylinders under the ends of the cross-shaped patch to form four capacitive loadings to lower the resonant frequency of the inner cross-shaped patch. A capacitive coupling feed structure is used to match the input impedance of a patch antenna and make the antenna compact enough. The simulated and measured results show that the proposed antenna can produce appropriate dual-band circularly polarized radiation patterns for precise satellite navigation. The measured results of the antenna illustrate that maximum RHCP gain of the antenna is 4.72 dBi in the low band and 3.98 dBi in the high band, the 3 dB gain bandwidth is 70 MHz in the low band and 65 MHz in the high band.